Legal and Ethical Implications in Data Theft Cases in the Digital Era - Hasudungan Sinaga (East Asian Journal of Multidisciplinary Research, 2023)
This research explores the legal and ethical implications in cases of data theft in the digital era in Indonesia. In the context of globalization and digitalization, personal data protection is very important to maintain individual privacy. However, Indonesia still does not have specific laws regarding personal data protection, although preventative efforts have been made. Factors such as lack of legal awareness among the public, lack of security in internet use, lack of knowledge of law enforcement officials, and lack of legislation present challenges in protecting personal data. The importance of legal certainty in protecting personal data demands the ratification of the Draft Law on personal data protection in Indonesia. Other countries such as the UK and Malaysia have ratify and legalize personal data protection laws to provide legal certainty to their citizens. Personal data protection must follow constitutional principles and involve cooperation between legislative, judicial and executive powers. In the judicial process, the principle of lex specialis derogat legi generali applies, allowing specific laws to override general provisions in criminal law. With the existence of specific personal data protection laws, people will feel safer and their privacy can be guaranteed in the era of increasingly advanced digitalization.